Milieus of Creativity An Interdisciplinary Approach to Spatiality of Creativity - Meusburger, Peter; Funke, Joachim; Wunder, Edgar (Knowledge and Space, 2009)
"Milieus of Creativity" is the second volume in the book series "Knowledge and Space". This book deals with spatial disparities of knowledge and the impact of environments, space and contexts on the production and application of knowledge. The contributions in this volume focus on the role of places, environments, and spatial contexts for the emergence and perpetuation of creativity. Is environment a social or a spatial phenomenon? Are only social factors relevant for the development of creativity or should one also include material artefacts and resources in its definition? How can we explain spatial disparities of creativity without falling victim to geodeterminism? This book offers insights from various disciplines such as environmental psychology, philosophy, and social geography. It presents the results of a research conference at Heidelberg University in September 2006, which was supported by the Klaus Tschira Foundation.